Implementing Differentiated Learning to Foster Learning Interest and Creative Thinking among Diverse Elementary School Students - Nurmala, Neli; Paik, Iik Nurul; Fitriani, Yulianti (Journal of Innovation and Research in Primary Education, 2025)
The quality of an abstract significantly influences readers’ decisions to engage with a scholarly article in its entirety. A well-structured abstract should encompass several key elements. The background of this study highlights the relevance and urgency of instructional approaches that can accommodate student diversity in primary education, where uniform teaching methods often overlook individual differences and risk diminishing both student engagement and academic achievement. The objective of this research is to identify and synthesize effective strategies for implementing differentiated instruction that simultaneously enhances learning interest and creative thinking skills among primary school students. Employing a descriptive qualitative approach through a literature review design, data were systematically collected from various academic databases, including Google Scholar, ResearchGate, and DOAJ, resulting in the selection of 13 studies based on stringent inclusion criteria. The findings indicate that differentiated learning strategies exert a significant positive impact on the development of creative thinking skills and the enhancement of students’ learning interest. A reciprocal relationship was identified, wherein heightened interest fosters creativity, and creative activities, in turn, stimulate interest in learning. In conclusion, this study proposes a conceptual framework to guide educators in implementing differentiated instruction within heterogeneous classrooms. The practical implications underscore the need to adopt flexible and responsive instructional models to maximize the potential of every learner.